2014
DOI: 10.1371/journal.pone.0108477
|View full text |Cite
|
Sign up to set email alerts
|

Paricalcitol Reduces Peritoneal Fibrosis in Mice through the Activation of Regulatory T Cells and Reduction in IL-17 Production

Abstract: Fibrosis is a significant health problem associated with a chronic inflammatory reaction. The precise mechanisms involved in the fibrotic process are still poorly understood. However, given that inflammation is a major causative factor, immunomodulation is a possible therapeutic approach to reduce fibrosis. The vitamin D receptor (VDR) that is present in all hematopoietic cells has been associated with immunomodulation. We investigated whether the intraperitoneal administration of paricalcitol, a specific acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 43 publications
5
51
0
Order By: Relevance
“…Gonzalez-Mateo et al (13) did not find a significant increase in peritoneal fluid TGF-β, IL-1b, IL-2, IL-4, IL-5, IL-6, IL-10, IFN-γ and TNF-α levels similar to our study when they evaluated the effect of paricalcitol on the fibrotic process in mice which undergoing peritoneal dialysis. They only found a statistically significant difference in IL-17 levels as paricalcitol reduced the IL-17 level in peritoneal fluid.…”
Section: Figure 1: Effects Of Paricalcitol Therapy On Peritoneal Permsupporting
confidence: 89%
See 4 more Smart Citations
“…Gonzalez-Mateo et al (13) did not find a significant increase in peritoneal fluid TGF-β, IL-1b, IL-2, IL-4, IL-5, IL-6, IL-10, IFN-γ and TNF-α levels similar to our study when they evaluated the effect of paricalcitol on the fibrotic process in mice which undergoing peritoneal dialysis. They only found a statistically significant difference in IL-17 levels as paricalcitol reduced the IL-17 level in peritoneal fluid.…”
Section: Figure 1: Effects Of Paricalcitol Therapy On Peritoneal Permsupporting
confidence: 89%
“…The interstitial extracellular matrix accumulation was also significantly reduced by treatment with paricalcitol. Gonzalez-Mateo et al (13) similarly showed that paricalcitol co-treatment significantly decreased peritoneal membrane thickness in rats that had undergone peritoneal dialysis. We found a correlation between increasing doses of paricalcitol co-treatment and decreased peritoneal membrane thickness.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 96%
See 3 more Smart Citations